Implementation Of Regional Government Affairs In Efforts To Protect Women In Gunungkidul District - Febriana Muryanto; Suryandari, Suryandari; Ari Dyah Sinta Tri Astuti; Monesta Cici Ijan; Munawara Salfitri (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to determine how the implementation of Gunungkidul Regency's local governmentaffairsin the field of women's empowerment and child protection, especially in efforts to protect women. The research method used is descriptive qualitative, with the data for this research coming from secondary sources,which are obtained from various literatures, such as scientific journals, books, research reports, andotherreliable sources. Secondary data was selected because this data has been verified and can provide a broader and deeper perspective on the topic under study. To check the validity of the data, researchers used a triangulation model, with data validity checking techniques that utilize various sources, methods, and theories to test the consistency of findings. In this study, triangulation was carried out by comparing and contrasting data obtained from various secondary sources. Technical data analysis in this study, researchers used data reduction, data presentation and conclusion drawing and data verification. The result of this research is that the implementation of regional government affairs in Gunungkidul Regency in efforts to protect women has been effective by showing high commitment through violence prevention programs, providing services forvictims, and strengthening protection service provider institutions, which reflects success in creating a strong and responsive women's protection system, although there are still problems and challenges that need to be addressed in the future.